Cross-border electronic banking : challenges and opportunities - Norton, Joseph Jude.; Reed, Chris; Walden, Ian.; Queen Mary and Westfield College (University of London).; Chartered Institute of Bankers (London ; New York : Lloyd's of London Press, 1995)
Addresses everything from the changes made to payment clearing since the deregulation of cross-border flows of funds, to the development of capital adequacy ratios and the Euro. This insightful and revealing book, backed up by extensive practical experience, will alert you to the ways that electronic banking practices affect even the simplest daily transactions, and will unveil the legal technicalities imposed by these developments.
"Published jointly with the Centre for Commercial Law Studies and the Chartered Institute of Bankers."
Includes bibliographical references and index.
aia 05/08/2016
Loans
Keywords: Banks and banking, International -- Automation; Banks and banking, International -- Law and legislation; Electronic funds transfers -- Law and legislation